PERAN PEMEDIASIAN KARAKTERISTIK INTI PEKERJAAN TERHADAP PENGARUH KEPEMIMPINAN TRANSFORMASIONAL PADA PERILAKU KERJA - NUR HASANAH (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
This research aimed to test the direct effects of transformational leadership positively to task performance and organizational citizenship behaviors. This research also aimed to test the mediating effect of core job characteristics toward the effects of transformational leadership on task performance and organizational citizenship behavior. The hypotheses were: (1a) Transformational leadership is positively and directly related to task performance, (1b) Transformational leadership is positively and directly related to organizational citizenship behavior; (2a) Core job characteristics mediate the effect of transformational leadership on task performance, (2b) Core job characteristics mediate the effect of transformational leadership on organizational citizenship behavior. Survey with questionnaires was held to obtain the data. 165 samples were collected from two organizations in Yogyakarta, with the overall response rate 81.85%. Respondents consist of supervisors and their immediate subordinates, from different kind of jobs, such as nursery administration, accounting, telephone operator, logistics, computer/technology, security, laboratory, etc. Unit analysis was individual. Multi-rater technique was used when collecting data in order to reduce common method bias. Using SEM with AMOS 16.0, results of the analysis showed that transformational leadership had indirect effects on task performance and organizational citizenship behaviors, through the full mediating role of core job characteristics.